BEBERAPA DIMENSI AKUNTANSI : MENURUT ALQUR'AN, MAHWAH, SEJARAH ISLAM DAN KINI - Sofyan Syafri Harahap (Media Riset Akuntansi, Auditing & Informasi, 2002)
Islamic Accounting is a new phenomenon. The emerging educated people from Islamic society produces a new machhe to revisit Islamic heredty in social, political, economics and business knowledge. The domination of capitalist accounting has influenced our social, political, economics as well as our accounting system. The discussion of Islamic Accounting has been started either by Non-Muslim scholar or Muslim Scholar At least there are three Ihews evlaining the form of Islamic Accounting: Islamic accounting based on Alguran, based on Islamic history applied by ''daulah Islamiyatf (Muslim govemment) and based on reconstruction from capitalist accounting system. Those three views will be discussed in this paper.Hai orang orang yang beriman masuklah kamu ke dalam Islam keseluruhan dan jangan kamu turut langkah Iangkah syaitan. Sesungguhnya syetan itu musuh nyata bagimu (Albaqarah 208)We are like a big fish that has been pulled from the water and is flopping wildly to find its way back in (Lester Thurow, 1996 The Future ofCapitalism)